2011
DOI: 10.1097/tp.0b013e3182384b21
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Dual Antibody Induction Therapy With Steroid Avoidance in Renal Transplantation

Abstract: These two distinct dual-induction therapies with rTd, EC-MPS, and planned early corticosteroid withdrawal resulted in favorable rates of BPAR and all secondary outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…Our prospectively followed cohort of 628 adult, primary kidney-alone transplant recipients consists of all participants in four randomized immunosuppression trials performed at our center since May 2000 (27, 46Y49 (100 patients per arm), with maintenance in both arms consisting of tacrolimus, enteric-coated mycophenolate sodium (using one-half of standard dose in the ATG/ alemtuzumab arm), and planned early corticosteroid withdrawal (49); last follow-up date was May 2010. The center institutional review board approved each protocol; all patients gave written informed consent before enrollment (Clinical Trials.gov ID: NCT00681213, NCT00685061, NCT00681343, NCT00533624, and NCT01172418).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Our prospectively followed cohort of 628 adult, primary kidney-alone transplant recipients consists of all participants in four randomized immunosuppression trials performed at our center since May 2000 (27, 46Y49 (100 patients per arm), with maintenance in both arms consisting of tacrolimus, enteric-coated mycophenolate sodium (using one-half of standard dose in the ATG/ alemtuzumab arm), and planned early corticosteroid withdrawal (49); last follow-up date was May 2010. The center institutional review board approved each protocol; all patients gave written informed consent before enrollment (Clinical Trials.gov ID: NCT00681213, NCT00685061, NCT00681343, NCT00533624, and NCT01172418).…”
Section: Data Descriptionmentioning
confidence: 99%
“…We were therefore interested in determining the prognostic impact of NODAT among patients receiving transplants at our centre. To maximise statistical power, we combined data for all study participants in four randomised immunosuppression trials of adult, primary kidney transplantation performed at our centre since May 2000 [22][23][24][25][26][27][28][29][30][31][32], yielding a prospectively followed cohort of 628 patients. Results from this observational study are presented here.…”
Section: Introductionmentioning
confidence: 99%
“…: NCT00681213, NCT00685061, NCT00681343, NCT00533624 and NCT01172418; note: two distinct registration numbers exist in the second trial, because separate randomisations of deceased donor and living donor recipients were performed). Results of these randomised trials have been reported previously (details omitted here) [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Most are case reports describing alemtuzumab as salvage or induction therapy. 123,163,[166][167][168][169][170][171][172][173][174][175][176] In a small group of lung transplant recipients with rejection refractory to steroids and ATG, alemtuzumab appeared to be effective in reversing rejection and bronchiolitis obliterans syndrome. 177 Treatment of rejection appears similarly effective in kidney transplant recipients but may be associated with increased early infection-related deaths.…”
Section: Alemtuzumab (Campath)mentioning
confidence: 99%